Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Dalam Menggunakan Layanan Shopeefood - Ahmad Haikal Aly; Budi Wahono; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research aims to assess the impact of the promotion & quality service of the ShopeeFood consumers contentment among management students at the Islamic University of Malang. This research used quantitative approach method, which includes survey research with the slovin formula for 86 respondents sampling. Furthermore, the data was collected through questionnaires using Google Forms to the population of Management Students. This research used Multiple linear Regression for analytical data methods. Based on the findings of this research indicate that both promotion and sercive quality had a significant impact on consumer contentment among ShopeeFood users. Keywords: Promotion, Service, ShopeeFood